A cross sectional study on optimal infant and young child feeding practices with reference to WHO indicators in a rural area of Puducherry - Radjasegarane, Arulprasad; Rajagopal, Anandaraj; Mathiyalagen, Prakash; Vasudevan, Kavita (International Journal Of Community Medicine And Public Health, 2019)
Background: Optimal infant and young child feeding practices (IYCF) are essential to address the increasing burden of malnutrition and for the overall development of the children. The present study was conducted to estimate the proportion of optimal infant and young child feeding practices among rural children aged 0 to 23 months and study the associated socio demographic factors. Methods: A community based cross-sectional study was conducted among 360 children in the age group of 0 to 23 months in a rural field practice area of a medical college in Puducherry. Data on IYCF practices were collected using a standardized tool developed by WHO. Core and optional IYCF indicators were calculated. Chi-square test and Fishers’ exact test were used as tests of significance. Results: Almost 88.0% of infants were initiated early on breastfeeding and 90.8% were exclusively breastfed for six months. Children who were continuously breastfed at one year and two years were 77.4% and 22.4% respectively. About 75.0% were introduced with solid or semisolid foods at 6 to 8 months of age. Among children aged 6 to 23 months, 77.3% had the recommended minimum dietary diversity, 81.3% had the minimum meal frequencies, while 57.7% received the minimum acceptable diet and only 39.4% consumed iron rich foods. Gender was significantly associated with the practice of continued breastfeeding at one year, adequate minimum dietary diversity and minimum meal frequency. Conclusions: The core and optional IYCF indicators were acceptably good in the initial six months of life but thereafter showed suboptimal levels, which should be emphasized among the mothers or primary care givers.